Neutron clusters in nuclear systems - Huang, Siwei; Yang, Zaihong (Frontiers in Physics, 2023)
Formation of neutron clusters from strongly correlated neutrons has become one of the hottest topics in nuclear physics. They lie at the heart of understanding the exotic structure of nuclei around the neutron drip line and provide an important basis for testing nuclear interactions due to the absence of Coulomb interaction and further developing theoretical models. Moreover, neutron clusters composed purely of neutrons could serve as a mini prototype of neutron matter to study the still elusive properties of the extremely neutron-rich nuclear matter, building a bridge between finite nuclei and neutron stars. In this paper, we will briefly review the recent highlights of experimental and theoretical works on neutron clusters.